A Blind Reversible Robust Watermarking Scheme for Relational Databases - Chin-Chen Chang; Thai-Son Nguyen; Chia-Chen Lin (The Scientific World Journal)
Protecting the ownership and controlling the copies of digital data have become very important issues in Internet-based applications. Reversible watermark technology allows the distortion-free recovery of relational databases after the embedded watermark data are detected or verified. In this paper, we propose a new, blind, reversible, robust watermarking scheme that can be used to provide proof of ownership for the owner of a relational database. In the proposed scheme, a reversible data-embedding algorithm, which is referred to as “histogram shifting of adjacent pixel difference” (APD), is used to obtain reversibility. The proposed scheme can detect successfully 100% of the embedded watermark data, even if as much as 80% of the watermarked relational database is altered. Our extensive analysis and experimental results show that the proposed scheme is robust against a variety of data attacks, for example, alteration attacks, deletion attacks, mix-match attacks, and sorting attacks.